Evaluation of the use of herbal drugs by pharmacy academics of Paranaense University Unity from Francisco Beltrão – PR - Brazil (Research, Society and Development, 2020)
This research aims to verify the knowledge and use of herbal medicines by students of pharmacy´s course of the University of Paranaense - UNIPAR, University Unit from Francisco Beltrão - PR. For this purpose, 29 students enrolled from first to fourth grade of the pharmacy course were investigated through the application of a questionnaire. 96% of the students were female and the average age was 20.7 years. Regarding the use of herbal medicines by academics, 72.4% said they had already used them, while 27.6% answered that they use them frequently, anyone reported that never used herbal medicines and 69% of all respondents reported use by self-medication. The main reasons that leads the students to use the herbal medicines were gastrointestinal disorders and anxiety. Regarding of adverse effects provocade by the use of herbal medicines, 86.2% of the students reported no adverse symptoms, and finally, it was questioned if the students believe that they have any knowledge about the area of herbal medicine, and 65.5% responded positively. In conclusion, it was observed that the students of the pharmacy course reported having knowledge and use of herbal medicines, mainly to revert disorders of the central and gastrointestinal nervous system, being most of the times by self medication.